Armas y escudos del amor: Dimensiones sociales del lenguaje en el Libro de buen amor - Ruiz, Carrie L. (Viator (English and Multilingual Edition), 2012)
Abstract This study examines the social dimensions of language in the Libro de buen amor (Book of Good Love.)Informed by the theories of Richard Bauman and Charles Briggs on language as a mediator in social praxis, I analyze how discourse functions as a mechanism to generate agency and confer power. This social dimension of language is exemplified, above all, through the figure of the go-between. Therefore, this study centers on the implementation of language by Trotaconventos as an effective means to invert her marginal position and gain social power. However, her discursive adroitness is challenged by other characters, especially in the episode of the Moorish woman, which offers a paradigm to resist the advances of the go-between. Thus, within the analysis of Trotaconventos’s discursive strategies, particular attention is given to this episode since it illustrates how the diverse uses of language in the text function to create social agency.